Assessing the Impact of ENSO on Agriculture Over Africa Using Earth Observation Data - Sazib, Nazmus; Mladenova, lliana E.; Bolten, John D. (Frontiers in Sustainable Food Systems, 2020)
The El Niño–Southern Oscillation (ENSO) is one of the strongest drivers of climate variability that directly influences agricultural production. The aim of this study is to assess the impact of ENSO on agriculture in Southern and Eastern Africa by (1) exploring the association between ENSO, vegetation condition and soil moisture, and (2) analyzing the difference in soil moisture and vegetation conditions for two extreme ENSO phases (El Niño and La Niña). Our results indicate that vegetation conditions are strongly associated with ENSO and show a clear dipole pattern that is reversed between El Niño and La Niña. Lagged correlation analysis confirms the ability of soil moisture and ENSO to predict vegetation conditions with 1–3 months of lead-time. The temporal and spatial evolution of soil moisture and vegetation responses showed the expected dipole pattern during the El Niño and subsequent La Niña events. Results indicate that ENSO impact on crop yield varies with geographical location, crop types, and ENSO phases. For example, yields in La Niña years have been higher in Southern Africa but lower in Eastern Africa. Maize yield decreases associated with El Niño events were usually larger than corresponding yield increases during La Niña events over Southern Africa. Our findings highlight the impact of ENSO on agricultural production, which has significant potential to enhance the early warning system for agriculture and food security.